Social determinants influencing cervical cancer diagnosis: an ecological study - Juan Fernando Galindo; Giovana Moura Formigari; Luiz Carlos Zeferino; Carla Fabrine Carvalho; Edson Luiz Ursini; Diama Bhadra Vale (BMC, 2023)
Abstract Background Barriers to accessing health care result in advanced cervical cancer. In Sao Paulo, Brazil, the Index of Social Responsibility (ISR) synthesizes the situation of each town concerning wealth, education, and longevity. This study aimed to evaluate in 645 municipalities the relation of the ISR with stage, age, and morphology in cervical cancer diagnosis. Methods An ecological study that used data from Sao Paulo, Brazil, from 2010 to 2017. The ISR was identified through government platforms and data on cancer through the Hospital Cancer Registry. The subjects were the 9,095 women aged 30 years or older. The ISR summarizes municipalities into five levels: dynamic (ISR5), unequal (ISR4), equitable (ISR3), in transition (ISR2), and vulnerable (ISR1). It was used the chi 2 tests and logistic regression. Results The proportion of stage 1 increased significantly with ISR level, ranging from 24.9% in ISR1 to 30.0% in ISR5 (p = 0.040). To every increase in ISR level, the chance of a woman being diagnosed in stage I was at least 30% higher. Woman living where ISR2 had a 1.4 times higher chance of being diagnosed in stage 1 than those living in ISR1 (OR 1.40, 95% CI 1.07-1.84). Squamous tumors frequency decreased when ISR level increased (p = 0.117). A higher proportion of women under 50 years were observed when they lived in wealthier cities (ISR4 and ISR5) (42.2% vs. 44.6%, p = 0.016). Conclusion The ISR was a good health indicator for understanding and predicting the social determinants in cervical cancer diagnosis. The proportion of stage I increased significantly in more favorable social conditions.